Association between red cell distribution width and risk of venous thromboembolism. Issue 3 (September 2015) - Bucciarelli, Paolo; Maino, Alberto; Felicetta, Irene; Abbattista, Maria; Passamonti, Serena M.; Artoni, Andrea; Martinelli, Ida
Abstract Background An association between high red cell distribution width (RDW) and venous thromboembolism (VTE) has been observed. However, it is not known whether this association differs within various manifestations of VTE, nor if there is an interaction between RDW and thrombophilia abnormalities on the risk of VTE. Aims To investigate whether RDW is a marker of the risk of VTE; to identify subgroups of patients in which the association between RDW and VTE is stronger; to investigate a possible interaction between RDW and thrombophilia abnormalities. Methods Case–control study on 730 patients with a first objectively-confirmed VTE episode (300 unprovoked and 430 provoked) consecutively referred to our Center between 2007 and 2013, and 352 healthy controls. Blood was taken for a thrombophilia work-up and a complete blood count, including RDW, at least three months after VTE. Results Individuals with RDW above the 90th percentile (> 14.6%) had a 2.5-fold increased risk of VTE compared to those with RDW ≤ 90th percentile, independently of age, sex, body mass index, other hematological variables and renal function (adjusted odds ratio: 2.52 [95%CI:1.42-4.47]). The risk was similar for unprovoked and provoked VTE, and slightly higher in patients with pulmonary embolism (adjusted odds ratio 3.19 [95%CI:1.68-6.09]) than in those with deep vein thrombosis alone (2.29 [95%CI:1.22-4.30]). No interaction between high RDW and thrombophilia abnormalities on the risk of VTE was observed. Conclusion Our findings confirm RDW as an independent and easily available marker for stratification of the risk of VTE.